Advances in Cryogenic Engineering 1966
DOI: 10.1007/978-1-4757-0522-5_53
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Forced Convection Boiling Heat Transfer Correlations for Cryogenic Fluids

Abstract: Hard copy (HC) a. bp Microfiche (M F) f50ff 863 JuIv 85

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…9, the wall temperature based on the film boiling correlation of Giarratano and Smith [24] is also shown. Apparently, the correlation of Giarratano and Smith [24] gives a very low heat transfer rate so that the wall temperature remains high. This comparison confirms our earlier argument that correlations based on the overall flow parameter, such as quality and averaged Reynolds number, are not applicable for the simulation of the unsteady chilldown.…”
Section: Discussion and Remarksmentioning
confidence: 85%
See 3 more Smart Citations
“…9, the wall temperature based on the film boiling correlation of Giarratano and Smith [24] is also shown. Apparently, the correlation of Giarratano and Smith [24] gives a very low heat transfer rate so that the wall temperature remains high. This comparison confirms our earlier argument that correlations based on the overall flow parameter, such as quality and averaged Reynolds number, are not applicable for the simulation of the unsteady chilldown.…”
Section: Discussion and Remarksmentioning
confidence: 85%
“…In Fig. 9, the wall temperature based on the film boiling correlation of Giarratano and Smith [24] is also shown. Apparently, the correlation of Giarratano and Smith [24] gives a very low heat transfer rate so that the wall temperature remains high.…”
Section: Discussion and Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…If this is true, then any available heat transfer correlations for normal liquid helium based on ground testing can be applied. Giarratano et al 22 suggested the correlation …”
Section: Nucleate Boiling Regimementioning
confidence: 98%